NDRG1 is a prognostic biomarker in breast cancer and breast cancer brain metastasis - Vaibhavi Joshi; Andrew Stacey; Yufan Feng; Priyakshi Kalita‐de Croft; Pascal HG Duijf; Peter T Simpson; Sunil R Lakhani; Amy E McCart Reed (The Journal of Pathology: Clinical Research, 2024)
Abstract Brain metastases are secondary brain tumours characterised by their aggressive nature and poor prognosis. Breast cancer is one of the most common primary tumours in women to spread to the brain. A lack of biomarkers predicting likely spread to the brain and limited therapeutic interventions represents major areas of clinical unmet need. We investigated N‐myc downregulated gene‐1 (NDRG1) as a clinically relevant biomarker in breast cancer brain metastasis patients. NDRG1 expression was investigated using immunohistochemistry on tissue microarrays of two clinical cohorts: (i) brain metastatic breast cancers (n = 48) and brain metastases (n = 64; including a subset of 39 patient‐matched breast and brain metastasis cases) and (ii) unselected primary breast cancers (n = 336). NDRG1 was highly expressed in breast‐to‐brain metastases, as well as in high‐grade primary breast cancers. High NDRG1 expression and also an absence of expression were associated with worse survival outcomes in both breast cancer and breast cancer brain metastasis patients. This establishes NDRG1 as a ‘Goldilocks’ protein, where too much or too little has a negative effect on survival. We pose that this accounts for its previous categorisation as both tumour suppressor and oncoprotein. Additionally, a shift in NDRG1 localisation with a gain of nuclear expression was seen at the brain metastasis stage. Significant survival benefit in cases expressing cytoplasmic NDRG1 was observed, whereas NDRG1 localisation in the nucleus showed a clear association with poorer survival. In vitro analyses revealed that hypoxic stress significantly elevated NDRG1 expression and resulted in its nuclear localisation. Our findings suggest NDRG1 expression and subcellular localisation are clinically relevant biomarkers for poor prognosis in breast cancer and breast cancer brain metastasis.